Hakikat Manusia dalam Perspektif Islam Serta Implikasinya pada Konseling Pendidikan Islam - Nurhasnah; Kenedi, Gusril; Afnibar, Afnibar; Ulfatmi, Ulfatmi; Yosnela, Tiwi Putria (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2023)
Counseling in Islamic education aims to help students gain an understanding of themselves and be able to solve the problems they face. For teachers in Islamic educational institutions, this goal requires them to first understand human nature in Islam to be able to carry out comprehensive counseling for students. This article was written to describe human nature and its implications for Islamic educational counseling activities today. This research was prepared using a qualitative approach with the type of literature study. The results of the research show that there are three terms used in the Qur’an to refer to humans, namely: al-insân (humans who have needs and have potential that can be developed), al-basyar (physical humans who look beautiful and perfect when compared with other creatures), and Banî Âdam (that all humans are descendants of Adam, both male and female. This includes all humankind on the face of the earth). Humans have two basic potentials, namely mind and heart, and nature. The purpose of human creation is to serve as caliph and to worship Allah SWT. In life, humans also have fundamental problems related to reason and passion which often do not go hand in hand. Humans have duties and responsibilities on earth as ’abd (servants of Allah SWT) and as caliphs. Based on this, the implication in Islamic education counseling is that counseling must encourage: understanding the purpose of life, developing nature, forming Islamic character, understanding duties as caliph, integrating knowledge with faith, forming social and humanitarian awareness, education as worship, understanding love and piety to Allah, holistic education, and the cultivation of a critical and creative spirit.